A comparative analysis of cardiopulmonary features in patients with systemic sclerosis and mixed connective tissue disease: results from SOPHIE registry - Mi Zhou; Mi Zhou; Bing-hua Wang; Ming-jiao Liao; Rui Yang; Jing Tan; Wen-jun Zhang; Chun-ka Wong; Chung-Wah Siu; Lixue Yin (Frontiers in Medicine)
PurposeWe aimed to identify various cardiopulmonary involvement patterns in patients with systemic sclerosis (SSc) and mixed connective tissue disease (MCTD).MethodsLaboratory experiments, pulmonary function test, 6-min walk distance (6MWD), transthoracic echocardiography, and 12-lead electrocardiography were used to evaluate cardiopulmonary function in patients with SSc and those with MCTD..ResultsA total of 138 patients with SSc and 56 patients with MCTD were enrolled in the study. Patients in the MCTD group exhibited a higher systolic blood pressure (SBP) (128.73 ± 16.82 vs. 121.95 ± 21.22, p = 0.03), diastolic blood pressure (DBP) (75.84 ± 10.96 vs. 70.79 ± 14.47, p = 0.02), and mean arterial pressure (MAP) (92.89 ± 13.02 vs. 87.17 ± 13.81, p = 0.009) compared to those in the SSc group. Levels of SaO2 at pre-6MWD (96.55 ± 2.61 vs. 98.67 ± 2.05, p < 0.001) and post-6MWD (95.73 ± 5.46 vs. 98.40 ± 2.73, p = 0.002) were markedly lower in MCTD patients compared to SSc patients. Laboratory analysis indicated that MCTD patients had lower platelet (PLT) counts (221.78 ± 71.88 vs. 253.96 ± 80.13, p = 0.01) and higher troponin T (TNT) (31.32 ± 74.85 vs.12.83 ± 16.30, p = 0.04) and brain natriuretic peptide (BNP) levels (193.35 ± 351.59 vs. 57.37 ± 53.68, p = 0.04) compared to patients with SSc. Pulmonary function tests revealed a decreased FEF50% predicted value (88.69 ± 44.58 vs. 122.86 ± 59.57, p < 0.001) and a higher proportion of patients with FEF75% predicted value <65% (28.26% vs. 10.71%, p = 0.009) in the SSc group compared to the MCTD group. Compared to SSc patients, patients with MCTD showed an increased left ventricular end-diastolic volume (LVEDV) (91.85 ± 32.87 vs. 73.32 ± 24.75, p < 0.001) and left ventricular end-systolic volume (LVESV) (30.59 ± 16.13 vs. 24.10 ± 8.99, p = 0.006), alongside decreased LVEF measured by the Simpson method (62.48 ± 6.33 vs. 66.58 ± 6.94, p < 0.001). Additionally, a higher proportion of patients in the MCTD group demonstrated a moderate or higher probability of pulmonary hypertension (PH) (39.29% vs. 13.04%, p = 0.000).ConclusionIn this cross-sectional analysis, we found small airway dysfunction in patients with SSc and impaired left ventricular systolic function in patients with MCTD. These findings indicate that there is significant heterogeneity in the cardiopulmonary involvement patterns, although these patterns are both connective tissue diseases with similar disease duration and comorbidity burden.